Local resource mobilisation in participatory planning: issues, constraints and potentialities - Mohanan, S. (2000)
A major advantage of local participatory planning is the possibility of tapping additional local resources. The resources for the local bodies include state assistance, own funds, assistance for state-sponsored schemes, assistance from centrally sponsored schemes, loans from co-operative institutions, loans from other financial institutions, voluntary contributions and beneficiary contributions. - Reproduced
Keywords: Local government - India; Local government